Sex specific EEG signatures associated with cerebrospinal fluid biomarkers in mild cognitive impairment. (October 2022) - Chino-Vilca, Brenda; Rodríguez-Rojo, Inmaculada Concepción; Torres-Simón, Lucía; Cuesta, Pablo; Vendrell, Anna Carnes; Piñol-Ripoll, Gerard; Huerto, Raquel; Tahan, Nuria; Maestú, Fernando
Highlights: EEG spectral power is a non-invasive approach for tracking AD neuropathology. This study contributes to the validity of EEG-based biomarkers for the early diagnosis of AD. Results provide potential sex-related differences regarding the association between EEG-CSF parameters. Abstract: Objective: The use of the electroencephalography (EEG) technique in Alzheimer's disease (AD) diagnosis is scarce due to a lack of validation of its neurophysiological information with current biomarkers. Therefore, our goal was to assess correlations between brain spectral power signatures and cerebrospinal fluid markers (CSF) such as amyloid-β 42 load (Aβ-42), total tau (t-tau), and phosphorylated tau (p-tau) in a mild cognitive impairment (MCI) population. Furthermore, given the AD sex-dependent vulnerability related to CSF biomarkers, we went a little forward looking for different electrophysiological correlations for males and females independently. Methods: A data-driven approach was employed to determine bidimensional spectral power signatures (space-frequency) that correlated (Spearman) significantly with any of the three CSF markers in 27 patients with MCI in any of the two sex-dependent subsamples (i.e., 12 females and 15 males). Results: Our main significant outcomes evidenced 1) a negative correlation of Aβ-42 load with central-posterior theta power and a negative correlation of t-tau with widespread alpha power within the male subsample, and 2) a significant negative correlation between t-tau and widespread beta power in the female subgroup. Conclusions: There is a distinctive profile of correlations between resting-state electrophysiological signatures and CSF markers in male and female individuals. Significance: The combination of these two measures would be pointing out the need of a more personalized approach to promote early AD diagnosis.